2017
DOI: 10.1161/hypertensionaha.116.08986
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Pressure, Heart Rate, and Cerebral Hemodynamics Across the Adult Life Span

Abstract: Age-related alterations in systemic and cerebral hemodynamics are not well understood. The purpose of this study is to characterize age-related alterations in beat-to-beat oscillations in arterial blood pressure (BP), heart rate (HR), cerebral blood flow (CBF), cardiac baroreflex sensitivity (BRS) and dynamic cerebral autoregulation (dCA) across the adult life span. We studied 136 healthy adults aged 21–80 years (60% women). Beat-to-beat BP, HR and CBF velocity were measured at rest and during sit-stand maneuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 41 publications
6
67
1
Order By: Relevance
“…In a population ranging in age from 21 to 80 years old, Xing et al. () reported lower VLF gain and higher phase during 0.05 Hz repeated squat‐stand maneuvers as compared with men, again suggesting a better dCA in women. In contrast to this investigation, Patel et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a population ranging in age from 21 to 80 years old, Xing et al. () reported lower VLF gain and higher phase during 0.05 Hz repeated squat‐stand maneuvers as compared with men, again suggesting a better dCA in women. In contrast to this investigation, Patel et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Xing et al. ) compared to age‐matched men. Of note, older women present less orthostatic symptoms or syncope than their younger counterparts (Romme et al.…”
Section: Introductionmentioning
confidence: 99%
“…In both conditions, heart rate variability was substantially reduced and cardiovagal baroreflex sensitivity was significantly attenuated in older adults compared with young adults (Xing et al . ). We also observed that low frequency CA gain is inversely correlated with the baroreflex gain in young subjects, as reported from a previous study (Tzeng et al .…”
Section: Age and Cbf Oscillationmentioning
confidence: 97%
“…Furthermore, augmented BP and CBF variability during repeated sit‐stand maneuvers indicate diminished cardiovascular regulatory capability in older adults and increased hemodynamic stress on the cerebral circulation with advanced aging (Xing et al . ).…”
Section: Age and Cbf Oscillationmentioning
confidence: 97%
“…In general, a brachial mean BP ≥60 mm Hg is thought to afford an adequate cerebral blood flow. Cerebral blood flow autoregulation may be affected in advanced age,49 by endotheliopathy, hypertension, diabetes mellitus,50 heart failure,51 hypocapnia, alkalosis, sympathetic arousal, autonomic failure,52 early after head injury, during an acute ischaemic stroke or during sepsis 53. The cerebral flow reserve also depends on the existence of cerebral small and large artery disease.…”
Section: Bp Goalsmentioning
confidence: 99%